2019
DOI: 10.1186/s13104-019-4285-1
|View full text |Cite
|
Sign up to set email alerts
|

Place for elective cholecystectomy for patients with severe thalassaemia: a retrospective case control study

Abstract: Objective At present, cholecystectomy is carried out for thalassaemia patients with gall stone disease only if they develop symptoms of cholecystitis, except in the rare instance where an un-inflammed gall bladder is removed simultaneously with splenectomy. We carried out this retrospective analysis of case records to examine if patients with thalassaemia have a higher rate of peri operative complications compared to non-thalassaemics with gall stone disease, warranting a change of policy to justi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…4 Children with thalassemia have a 10 -20% higher risk of cholelithiasis compared to the general population, often remains asymptomatic for many years. 2 This was the a. b.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…4 Children with thalassemia have a 10 -20% higher risk of cholelithiasis compared to the general population, often remains asymptomatic for many years. 2 This was the a. b.…”
Section: Discussionmentioning
confidence: 90%
“…However, it often remains asymptomatic for many years. 2 Management for non-thalassemic patients with cholelithiasis is usually conservative unless signs of cholecystitis or cholangitis were found. However, due to the increased risk of complications, a tailored approach is required for managing cholelithiasis in thalassemia patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu and colleagues found that surgical interventions for asymptomatic gallstones in patients with hereditary spherocytosis necessitating splenectomy were linked to a reduced risk of adverse outcomes 9 . Premawardhena et al strongly advocated that elective LC should be considered in patients with thalassemia to prevent the onset of serious complications associated with LC in symptomatic patients 10 .…”
Section: Discussionmentioning
confidence: 99%